Sudden coronary death, fatal acute myocardial infarction and widespread coronary and myocardial inflammation. Issue 6 (13th August 2007) - Abbate, A; Bussani, R; Liuzzo, G; Biondi-Zoccai, G G L; Barresi, E; Mellone, P; Sinagra, G; Dobrina, A; De Giorgio, F; Sharma, R; Bassan, F; Severino, A; et al.
Abstract : Background: T-lymphocyte activation within atherosclerotic plaque, and widespread to the myocardium, has been shown in patients with acute coronary syndromes. Objective: To investigate the presence of T-lymphocyte infiltrate at different stages of acute coronary syndromes by studying patients with sudden coronary death, acute myocardial infarction (AMI) and healed infarction, in comparison with patients with myocarditis and patients with non-ischaemic heart failure. Methods: 72 cases were studied at autopsy: 12 dying of sudden coronary death (group 1), 12 dying <4 weeks (group 2) and 12 dying >4 months after AMI (group 3), 12 with active lymphocytic myocarditis (group 4), 12 with hypertensive heart disease (group 5), and 12 control subjects (group 6). Light microscopy was performed to measure the number of activated T-lymphocytes (CD3+/DR+) in the myocardium and coronary artery wall, and intercellular adhesion molecule-1 (ICAM-1) expression in the myocardium. Results: Activated T-lymphocyte infiltrates and ICAM-1 myocardial expression in both remote and peri-infarction regions and activated T-lymphocytes within the epicardial coronary artery wall of both the infarct- and non-infarct-related arteries were found in groups 1, 2 and 3, whereas myocardial, but not coronary, infiltrates were found in groups 4 (p<0.001 vs groups 1, 2 and 3 for coronary infiltrates). Groups 5 and 6 had no evidence of myocardial or coronary inflammation (p<0.001 vs groups 1, 2 and 3). Conclusions: The study shows the presence of a lymphocytic infiltrate in both coronary arteries and myocardium and a proinflammatory phenotype shift in the myocardium associated with acute coronary thrombosis in patients dying suddenly, shortly, or even late after coronary thrombosis.